(untitled) (Research, Society and Development, 2022)
Autism spectrum disorder (ASD) is defined as a behavioral condition in which the child presents impairments or basic changes in behavior and social interaction, difficulties in communication, verbal and non-verbal acquisition, cognitive changes and the presence of repetitive or stereotyped behaviors. It is increasingly clear that genetics is primarily responsible for the origin of autism. Allied to this, isolated factors can also participate in the origin of autism, and environmental components would be serious insults to the developing fetal brain during the gestational period, as well as gestational factors unique to the mother, such as advanced age of the parents, gestational diabetes mellitus, preeclampsia, rubella infection and toxoplasmosis. The study also addresses protective factors, intrinsic to the mother, such as the use of folic acid, vitamin D, zinc, omega 3 and maternal breastfeeding.